Investigation of Surrogate Biomarkers Associated with Macular Pigment Status in a Group of Older Irish Adults. Issue 10 (October 2020) - Scanlon, Grainne; Butler, John S.; McCartney, Daniel; Loskutova, Ekaterina; Kenny, Rose A.; Loughman, James
Abstract : SIGNIFICANCE: Macular pigment (MP) confers potent antioxidant and anti-inflammatory effects at the macula; however, its optical density in the eye is not routinely measured in clinical practice. PURPOSE: This study explored a range of surrogate biomarkers including anthropometric, clinical, and plasma measures that may be associated with lower MP optical density (MPOD). METHODS: Two thousand five hundred ninety-four subjects completed a full MP assessment as part of wave 1 of The Irish Longitudinal Study of Aging. Macular pigment optical density was measured using customized heterochromatic flicker photometry. Clinical (blood pressure), plasma (lipoproteins, inflammatory markers), and anthropometric (waist, hip, height, weight) biomarkers were measured for each participant. RESULTS: Mean (standard deviation) MPOD for the study group was 0.223 (0.161), with a range of 0 to 1.08. One-way ANOVA revealed that MPOD was significantly lower among participants with low plasma high-density lipoprotein (HDL; P = .04), raised plasma triglyceride-to-HDL ratio ( P = .003), and raised total cholesterol–to–HDL ratio ( P = .03). Subjects with an elevated waist circumference (WC) had a significantly lower MPOD (mean, 0.216 [0.159]) compared with those with an ideal WC (mean, 0.229 [0.162]; P = .03). Significant correlates of MPOD on mixed linear model analysis included education, smoking status, and WC. CONCLUSIONS: Higher abdominal fat is associated with lower MPOD in this representative sample of older Irish adults. Although altered lipoprotein profiles (low HDL, raised triglyceride-to-HDL ratio, raised total cholesterol–to–HDL ratio) may affect the transport, uptake, and stabilization of carotenoids in the retina, these plasma biomarkers were not predictive of low MPOD after adjustment for abdominal circumference. Although WC emerged as a viable anthropometric predictor of lower MPOD, its effect size seems to be small.